TINJAUAN RUANG ASPEK KENYAMANAN RUANG PENYIMPANAN REKAM MEDIS DI PUSKESMAS KRAMATWATU - Heru Indra Cahya; Erwin Muhtaddin (Journal Of Applied Health Research And Development, 2022)
Background : The security of the medical record file storage room is one of the main parts to support the security of the medical record file, besides that there are still many health care facilities that underestimate the security of the medical record file storage room, look down on the eyes, and consider trivial things for the security of the record file storage room. medical records in addition to the security of the medical record file itself. The purpose of this study was to find out the review of the Security Aspects of the Medical Record File Storage Room at the Kramatwatu Health Center, South Tangerang. This research uses descriptive research method. From the results of observations and interviews, it was found that the SOP regarding the security of the medical record storage room was already available, but in its application it was still not optimal due to space limitations, the available storage space is not 100% in accordance with the criteria. The cleanliness aspect of the medical record file storage room is not fully appropriate, there is no fixed schedule for cleaning the medical record room, and the APAR is not yet available specifically in the medical record storage room. The conclusion of this study is that there is no SOP for work instructions and the safety of the medical record file storage room, the storage space in the Puskesmas has not been able to accommodate the available medical record files. APAR is not yet available specifically in the medical record storage room. The conclusion of this study is that there is no SOP for work instructions and the safety of the medical record file storage room, the storage space in the Puskesmas has not been able to accommodate the available medical record files. APAR is not yet available specifically in the medical record storage room. The conclusion of this study is that there is no SOP for work instructions and the safety of the medical record file storage room, the storage space in the Puskesmas has not been able to accommodate the available medical record files. APAR is not yet available specifically in the medical record storage room